Effect of dental pain and caries on the quality of life of Brazilian preschool children - Maria do Carmo Matias Freire; Patrícia Corrêa-Faria; Luciane Rezende Costa (Universidade de São Paulo, 2018)
ABSTRACT OBJECTIVE To investigate the impact of dental pain on daily performances among five-year-old Brazilian children. METHODS The study used data of 7,280 five-year-old children participating in the 2010 Brazilian Oral Health Survey (SBBrasil 2010 Project). Children were clinically examined and their parents or carers were interviewed at their homes. The outcome was the prevalence of the oral impacts on daily performance, and the explanatory variable was dental pain in the last six months. Other independent variables were children's gender and skin color/race, family income, household overcrowding, and caries experience (dmft). Rao-Scott test and Poisson regression for complex samples were carried out. RESULTS The prevalence of impacts on daily performances was 26.1% (95%CI 22.3-30.2). Significant associations were found between the outcome and pain, caries experience, and sociodemographic variables. After adjusting for the independent variables, only pain and caries remained significant. Impacts on daily performances were more frequent among children with pain (PR = 1.14, 95%CI 1.06-1.23) compared to those without pain. Children with low dmft (PR = 1.90, 95%CI 1.39-2.60) and those with high dmft (PR = 3.53, 95%CI 2.78-4.49) had a higher prevalence of impact than those with no caries experience. CONCLUSIONS Dental pain and caries had strong negative impacts on the five-year-old children's daily performances regardless of their demographic and socioeconomic characteristics.